IMPLEMENTASI METODE FINGER PAINTING DALAM MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK KARTIKA II-30 LAMPUNG TENGAH - Yuliawati, Eni (UNISAN JURNAL, 2025)
Finger painting is a learning method that integrates art and creativity elements to develop fine motor skills in early childhood. Fine motor skills are crucial for children aged 4-5 years as they directly relate to the ability to control hand and finger movements, which are fundamental for writing, drawing, and other daily activities. This study aims to determine the effect of implementing the finger painting method on improving fine motor skills of children aged 4-5 years at TK Kartika II-30 Lampung Tengah. The research employs a Classroom Action Research approach involving 20 children as research subjects. The results indicate a significant improvement in children's fine motor skills following the application of the finger painting method. Children demonstrated increased dexterity in finger movements, hand coordination, and correct grasping and holding of writing tools. Furthermore, the finger painting method also enhanced children's creativity and self-expression during the learning process. Children appeared more enthusiastic and motivated to participate in learning activities, creating a lively and conducive classroom atmosphere. This study proves that finger painting is an effective learning medium to improve fine motor skills in early childhood. Therefore, it is recommended that early childhood teachers at TK Kartika II-30 Lampung Tengah and similar institutions optimize the use of this method within their daily learning curricula to support holistic motor and creative development in children. The study also identified challenges such as limited materials and the need for extra supervision, which can be addressed through proper planning and management.